2010
DOI: 10.1089/ten.tea.2009.0786
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Mesenchymal Stem Cells Induce Mechanically Stable Posterior Spine Fusion

Abstract: Most spine fusion procedures involve the use of prosthetic fixation devices combined with autologous bone grafts rather than biological treatment. We had shown that spine fusion could be achieved by injection of bone morphogenetic protein-2 (BMP-2)-expressing mesenchymal stem cells (MSCs) into the paraspinal muscle. In this study, we hypothesized that posterior spinal fusion achieved using genetically modified MSCs would be mechanically comparable to that realized using a mechanical fixation. BMP-2-expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Most of the studies showing skeletal advantages with MSC therapy were performed by using local injection method in models of fracture healing, 28 calvarial defect, 29 or spinal fusion. 30 In our previous study, we found that systemically administrated murine BMMSC could effectively prevent bone loss after OVX, 18 and here we validated that xenotransplantation of human ADSC could similarly protect against OVX-induced bone mass attenuation, suggesting that systemic therapy of MSCs might have therapeutic potential. In this study we used T cell deficient mice to avoid immune response against human cell transplantation.…”
Section: Discussionsupporting
confidence: 67%
“…Most of the studies showing skeletal advantages with MSC therapy were performed by using local injection method in models of fracture healing, 28 calvarial defect, 29 or spinal fusion. 30 In our previous study, we found that systemically administrated murine BMMSC could effectively prevent bone loss after OVX, 18 and here we validated that xenotransplantation of human ADSC could similarly protect against OVX-induced bone mass attenuation, suggesting that systemic therapy of MSCs might have therapeutic potential. In this study we used T cell deficient mice to avoid immune response against human cell transplantation.…”
Section: Discussionsupporting
confidence: 67%
“…Our system is the first approach reported in the literature to achieve clinically relevant spinal fusion in an animal model within 2 weeks through a single intramuscular injection. Although it can be argued that several other systems achieve this goal in various animal models [2528], each of these studies fall short of a clinically relevant regimen. In a study by Hasharoni et al [25], the authors inject recombinant human BMP2–producing mesenchymal stem cells (MSCs) into the paraspinous muscles of immune-deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of the literature strongly supports the need for preconditioning or enhancement of osteogenic capability to dismiss the requirement for excessive cell doses. To this end, genetic modification of osteoprogenitor cells to allow the cells to produce bioactive molecules such as BMP2 [71,76,77] or vascular endothelial growth factor [71] has been performed with some success. However, as with any form of genetic modification, there are serious safety concerns.…”
Section: Discussionmentioning
confidence: 99%